Pilot study characterizing a single pooled preparation of equine platelet lysate for nebulization in the horse - Egli, Patricia; Boone, Lindsey; Huber, Laura; Higgins, Courtney; Gaonkar, Pankaj P.; Arrington, Justine; Naskou, Maria C.; Peroni, John; Gordon, Julie; Lascola, Kara M. (Frontiers in Veterinary Science, 2024)
IntroductionPlatelet lysate (PL) demonstrates antimicrobial and anti-inflammatory properties offering potential for treatment of bacterial pneumonia in horses. It remains unknown whether nebulization is suitable for PL administration in horses. This pilot study characterized particle size and flow rate of pooled equine PL (single preparation) nebulized using an equine-specific nebulizer (Flexivent®).MethodsProtein composition and antimicrobial activity were compared before and after nebulization. Protein composition was evaluated according to growth factor, antimicrobial peptide and cytokine concentrations and proteomic analysis. To evaluate antimicrobial activity, bacterial growth inhibition [maximum growth (μmax); carrying capacity (K)] were determined for E. coli, Streptococcus equi subsp zooepidemicus and Rhodococcus equi (WT and MDR) using pre- and post-nebulized PL concentrations of 50%.ResultsFlow rate and median particle size were 0.8 ml/min and 4.991 μm with 52% of particles ≤ 5 μm. Differences in PL protein composition were detected with nebulization. For E. coli and S. zooepidemicus, nebulization did not alter effect of PL on growth parameters. PL treatments decreased K for S. zooepidemicus (p = 0.009) compared to BHI. For R. equi K was increased post- vs. pre-nebulization (WT and MDR) and μmax increased pre- vs, post-nebulization (MDR). PL treatments increased K and μmax for MDR R. equi and μmax for WT R. equi compared to BHI (p ≤ 0.05).ConclusionNebulization of PL in vitro is technically feasible. The results of this study support further investigation to better characterize the effect of nebulization on PL and its suitability for nebulization in horses.